2014
DOI: 10.1016/j.devcel.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Levels Modulate Primitive Endoderm Cell Fate Choice and Timing in the Mouse Blastocyst

Abstract: SUMMARY Cells of the inner cell mass (ICM) of the mouse blastocyst differentiate into the pluripotent epiblast (EPI) or the primitive endoderm (PrE), marked by the transcription factors NANOG and GATA6, respectively. To investigate the mechanistic regulation of this process, we applied an unbiased, quantitative, single-cell resolution image analysis pipeline, to analyze embryos lacking or exhibiting reduced levels of GATA6. We find that Gata6 mutants exhibit a complete absence of PrE, and demonstrate that GATA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
269
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(307 citation statements)
references
References 48 publications
23
269
0
2
Order By: Relevance
“…Jens-Erik Dietrich et al Venus trap in the mouse embryo EMBO reports may be largely driven by asymmetric division, while that for the ICM marker may not be following the same mechanism. The mechanism regulating the ICM marker expression remains elusive, and the initiation of expression appears stochastic in the morula and early blastocyst stages without obvious correlation with position and the future lineage [4,8]. This finding is in line with our recent single-cell gene expression profiling study demonstrating genome-wide stochastic gene expression in the inner cells of the 32-cell stage blastocyst [7].…”
Section: à5supporting
confidence: 79%
“…Jens-Erik Dietrich et al Venus trap in the mouse embryo EMBO reports may be largely driven by asymmetric division, while that for the ICM marker may not be following the same mechanism. The mechanism regulating the ICM marker expression remains elusive, and the initiation of expression appears stochastic in the morula and early blastocyst stages without obvious correlation with position and the future lineage [4,8]. This finding is in line with our recent single-cell gene expression profiling study demonstrating genome-wide stochastic gene expression in the inner cells of the 32-cell stage blastocyst [7].…”
Section: à5supporting
confidence: 79%
“…Nanog-deficient mouse embryos are arrested during post-implantation development because of the widespread expression of Gata6 in the EPI (Mitsui et al 2003, Frankenberg et al 2011. By contrast, Gata6-deficient mouse embryos are arrested during postimplantation development because of the widespread expression of Nanog in the PE (Morris et al 2010, Schrode et al 2014. In the present study, we showed that Smyd3 knockdown led to the suppression of the embryonic transcription of Oct4 during the four-cell stage.…”
Section: Discussionmentioning
confidence: 47%
“…In mouse preimplantation embryos, Oct4, Nanog, and Sox2 are required for the maintenance of ICM pluripotency (Nichols et al 1998, Avilion et al 2003, Mitsui et al 2003. Additionally, Nanog is known to negatively interact with Gata6, and both genes are known to be key regulators in the establishment of EPI and PE fates respectively (Morris et al 2010, Frankenberg et al 2011, Kang et al 2013, Schrode et al 2014. Nanog-deficient mouse embryos are arrested during post-implantation development because of the widespread expression of Gata6 in the EPI (Mitsui et al 2003, Frankenberg et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression levels of the neuroectoderm marker ASCL1 (a transcription factor also known as MASH1) [22,23] were significantly upregulated ( Figure 2C, P < 0.05). The expression levels of the primitive endoderm marker GATA6 [24,25], encoding a transcription factor, were also upregulated, and those of the trophectoderm marker CDX2 [26,27], also encoding a transcription factor, were transiently upregulated during the progression of differentiation. The expression of endogenous TPRX1 mRNA was almost undetectable, whereas exogenous TPRX1 mRNA in NT2/D1 cells transfected with a TPRX1 expression vector (+FLAG/TPRX1) was clearly detected ( Figure 2D).…”
Section: Resultsmentioning
confidence: 91%